2022
DOI: 10.1007/s11682-021-00621-6
|View full text |Cite
|
Sign up to set email alerts
|

Pain’s Adverse Impact on Training-Induced Performance and Neuroplasticity: A Systematic Review

Abstract: Motor training is a widely used therapy in many pain conditions. The brain’s capacity to undergo functional and structural changes i.e., neuroplasticity is fundamental to training-induced motor improvement and can be assessed by transcranial magnetic stimulation (TMS). The aim was to investigate the impact of pain on training-induced motor performance and neuroplasticity assessed by TMS. The review was carried out in accordance with the PRISMA-guidelines and a Prospero protocol (CRD42020168487). An electronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 58 publications
(165 reference statements)
1
9
0
Order By: Relevance
“…No studies have explored activity dependent plasticity using functional MRI. The findings in this review are consistent with a systematic review by Stanisic et al [ 23 ] who reported acute experimental pain may influence training induced neuroplasticity defined by TMS. The authors suggested the impact of pain on training induced neuroplasticity may be dependent on the motor learning paradigms utilised.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…No studies have explored activity dependent plasticity using functional MRI. The findings in this review are consistent with a systematic review by Stanisic et al [ 23 ] who reported acute experimental pain may influence training induced neuroplasticity defined by TMS. The authors suggested the impact of pain on training induced neuroplasticity may be dependent on the motor learning paradigms utilised.…”
Section: Discussionsupporting
confidence: 92%
“…Two systematic reviews [ 22 , 23 ] have been recently published in this area. Izadi et al [ 22 ] investigated the impact of acute experimental pain on behavioural performance following motor learning.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It could be speculated that pain caused by NGF-induced sensitization could help bruxers unlearn or “detrain” repetitive masticatory muscle activity, changing their oral behavior 11 . Indeed, our findings may have implications in motor learning and performance understanding, with a putative impact on rehabilitative procedures such as physiotherapy 26 . Since everyone has potential biological prerequisites and resources developed through the course of life our findings providing a better knowledge on orofacial pain and function and its assessment and strategies for management 8 .” The effect of pain on jaw-closing muscle performance has been a subject of interest in earlier experimental studies 10 , 23 , applying or not methods to distinguish bruxers or non-bruxers participants.…”
Section: Discussionmentioning
confidence: 85%
“…In the pain field, a rapid effect of pain on cortical motor plasticity has been observed in response to acute and chronic pain 25 , which may impede training-induced functional neuroplasticity manifested as decreased corticomotor excitability as defined by TMS 26 . Sensory-motor integration at a reflex such as a motor withdrawal reflex in response to noxious stimuli acts as a protective response to noxious stimulation 25 .…”
Section: Discussionmentioning
confidence: 99%